Response to diet‐induced obesity produces time‐dependent induction and progression of metabolic osteoarthritis in rat knees. Issue 6 (2nd December 2015) - Collins, Kelsey H.; Hart, David A.; Reimer, Raylene A.; Seerattan, Ruth A.; Herzog, Walter
ABSTRACT: Obesity, and corresponding chronic‐low grade inflammation, is associated with the onset and progression of knee OA. The origin of this inflammation is poorly understood. Here, the effect of high fat, high sucrose (HFS) diet induced obesity (DIO) on local (synovial fluid), and systemic (serum) inflammation is evaluated after a 12‐week obesity induction and a further 16‐week adaptation period. For 12‐weeks of obesity induction, n  = 40 DIO male Sprague–Dawley rats consumed a HFS diet while the control group ( n  = 14) remained on chow. DIO rats were allocated to prone (DIO‐P, top 33% based on weight change) or resistant (DIO‐R, bottom 33%) groups at 12‐weeks. Animals were euthanized at 12‐ and after an additional 16‐weeks on diet (28‐weeks). At sacrifice, body composition and knee joints were collected and assessed. Synovial fluid and sera were profiled using cytokine array analysis. At 12‐weeks, DIO‐P animals demonstrated increased Modified Mankin scores compared to DIO‐R and chow ( p  = 0.026), and DIO‐R had higher Mankin scores compared to chow ( p  = 0.049). While numerous systemic and limited synovial fluid inflammatory markers were increased at 12‐weeks in DIO animals compared to chow, by 28‐weeks there were limited systemic differences but marked increases in local synovial fluid inflammatory marker concentrations. Metabolic OA may manifest from an initial systemic inflammatory disturbance. Twelve weeks of obesity induction leads to a unique inflammatory profile and induction of metabolic OA which is altered after a further 16‐weeks of obesity and HFS diet intake, suggesting that obesity is a dynamic, progressive process. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1010–1018, 2016.